DECONSTRUCTING INDUSTRIAL REVOLUTION 4.0 DISCOURSE IN EDUCATIONAL INEQUALITY IN INDONESIA - Moch. Gilang Ramadhan; Elly Malihah Setiadi; Siti Nurbayani (Universitas Negeri Medan, 2024)
Research with the topic of deconstructing industrial revolution 4.0 discourse is become important to provide awareness that except spiritual concepts, absolute truth cannot exist. In the discourse of Industrial Revolution 4.0, we must see the truth as separated fragments. The discourse of the industrial revolution 4.0, is born and forced to become a new regime of truth in society. Knowledge and enthusiasm regarding the discourse of the industrial revolution 4.0 which is disseminated systematically and then manifested into regulations actually curbs people's way of thinking. Therefore, this research aims to examining overlooked meanings, or even presenting a different perspective with critical analysis regarding industrial revolution discourse in education. And also revise the facts behind the belief and enthusiasm for the industrial revolution 4.0 discourse. This research uses a qualitative approach, with a literature study method, so that data is obtained through reviewing various scientific journals related to the research theme. Research findings show 1) industrial revolution 4.0 discourse was formed because the state positioned education as an opportunity for economic activity, which then had to be adapted and lead to children's investment in the future through education, 2) The delegation of quality education to the private sector and the reduced role of the state are caused by neoliberal discourse. Problems then arise when the discourse on industrial revolution 4.0 actually ignores the right to an equitable and prosperous life and further sharpens inequality in society, 3) Each social class has different habits (habitus) to respond to readiness for the industrial revolution 4.0. Starting from media ownership and access to learning, to family cultural factors and the absence of the state in important areas of learning.